2017
DOI: 10.7860/jcdr/2017/30705.10529
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis of Liver and Diabetes Mellitus: The Diabolic Duo?

Abstract: Coexistent diabetes mellitus increases the incidence of complications and hospitalizations in cirrhosis patients but without impact on mortality rates. There is no significant morbidity or mortality difference between cirrhotics with antecedent diabetes and hepatogenous diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Despite all the beneficial interventions implemented in patients with diabetes, including tight glucose control and tight blood pressure control with regimens that inhibit the renin angiotensin aldosterone system, renal disease still progresses in most diabetic patients. Diabetes is associated with a series of liver diseases including nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), cirrhosis, fulminant hepatic failure and hepatocellular carcinoma [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the beneficial interventions implemented in patients with diabetes, including tight glucose control and tight blood pressure control with regimens that inhibit the renin angiotensin aldosterone system, renal disease still progresses in most diabetic patients. Diabetes is associated with a series of liver diseases including nonalcoholic fatty liver disease (NAFLD), nonalcoholic steatohepatitis (NASH), cirrhosis, fulminant hepatic failure and hepatocellular carcinoma [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies showed a greater risk for developing urinary infections [ 32 ], SBP and others, while DM was independently associated with bacterial infections in cirrhotic patients with HCV [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results and conclusions presented here are based on systematically collected data from 3 multicentre trials. Out of 5 studies previously published within this area, 4 reported a relative risk of infections of >2.5 in patients with cirrhosis and diabetes compared to those with cirrhosis without diabetes [17][18][19][20][21] (Table S1). One possible way to explain the discrepancy with our findings is that cirrhosisin its most severe, decompensated stateconfers such an overwhelming risk of infections that any additional risk by diabetes becomes difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…One possible way to explain the discrepancy with our findings is that cirrhosisin its most severe, decompensated stateconfers such an overwhelming risk of infections that any additional risk by diabetes becomes difficult to detect. Most of those previous studies did not describe the severity of cirrhosis, [17][18][19][20] but one of them was limited to patients with compensated cirrhosis 21 (Table S1). It found an HR for infections of 4.08 (95% CI 1.43-11.66) among patients with cirrhosis due to hepatitis B infection, but did not attempt to control for confounding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation